Application of Deep Learning-Based Methods to the Single Image Non-Uniform Blind Motion Deblurring Problem - Shoyan, Misak T.; Hakobyan, Robert G.; Shoyan, Mekhak T. (Mathematical Problems of Computer Science, 2021)
In this paper, we present deep learning-based blind image deblurring methods for estimating and removing a non-uniform motion blur from a single blurry image. We propose two fully convolutional neural networks (CNN) for solving the problem. The networks are trained end-to-end to reconstruct the latent sharp image directly from the given single blurry image without estimating and making any assumptions on the blur kernel, its uniformity, and noise. We demonstrate the performance of the proposed models and show that our approaches can effectively estimate and remove complex non-uniform motion blur from a single blurry image.